The Rise and Decline of the American Century - Walker, William O., III, 1946- (Book collections on Project MUSE., 2018)
"More than waging cold war, efforts to forge an American Century defined the course of U.S. foreign policy from 1945 through 1968. Henry R. Luce's call in 1941 for an American Century gave shape to four decades of thinking about how the United States should engage the world"--